2018
DOI: 10.1016/j.jflm.2018.07.013
|View full text |Cite
|
Sign up to set email alerts
|

The exploitation of fresh remains by Dermestes maculatus De Geer (Coleoptera, Dermestidae) and their ability to cause a localised and prolonged increase in temperature above ambient

Abstract: This article discusses the ability of adults of the coleopteran beetle Dermestes maculatus (De Geer) to colonise fresh remains. It also considers whether colonisation results in localised thermogenesis in a similar manner to that induced by blowfly larvae. In the laboratory, adult D. maculatus instantly colonised fresh killed rats and mice. The adults entered the oral cavity within 1-2 h and the eyes and ears were among the first parts of the body consumed. Egg laying occurred on the torso and head within an h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 24 publications
0
7
0
Order By: Relevance
“…been recognized as a significant component of the insect fauna associated with decomposing remains, both human and animal, and it can be present at different stages of decomposition, even early ones [19][20][21]. Although these beetles have adaptations for feeding on dry materials, studies performed under controlled conditions allow clarification that dermestids are able to colonize, feed and reproduce on fresh tissues soon after death [22,23]. Equally, Samish et al [24] reported that these beetles caused deep wounds on live turkeys.…”
Section: Dermestes Maculatus De Geer Is a Cosmopolitan Species And Hasmentioning
confidence: 99%
“…been recognized as a significant component of the insect fauna associated with decomposing remains, both human and animal, and it can be present at different stages of decomposition, even early ones [19][20][21]. Although these beetles have adaptations for feeding on dry materials, studies performed under controlled conditions allow clarification that dermestids are able to colonize, feed and reproduce on fresh tissues soon after death [22,23]. Equally, Samish et al [24] reported that these beetles caused deep wounds on live turkeys.…”
Section: Dermestes Maculatus De Geer Is a Cosmopolitan Species And Hasmentioning
confidence: 99%
“…The Dermestidae family includes over 1000 species globally (1), with about 130 species in the United States (2). Insects in the Dermestes genus prefer to feed on the dry remains of animal tissue during decomposition (2,3), although under certain conditions they have been shown to colonize fresh remains (4). Specifically, the species Dermestes maculatus De Geer 1774, distinguished from other species within the Dermestes genus by having a white abdomen with black markings (1,5) (Figs 1–3), have a natural propensity to consume soft tissue throughout various stages of decomposition.…”
Section: Figmentioning
confidence: 99%
“…In a forensic context, they are often observed on human corpses during late decomposition stages, but have also been sampled as early as 10 days after death [ 1 , 2 , 3 ]. During colonization, larder beetles accelerate the skeletonization process at varying rates depending on population composition and density, body size, ambient temperature, or the amount of food available [ 4 , 5 , 6 ]. They are found in indoor as well as outdoor environments, especially in areas with dry weather or during warm months with low rainfall [ 7 ].…”
Section: Introductionmentioning
confidence: 99%